A COMBINATION OF CHEEK FLAP, CARTILAGE INSERTION, AND FAT TRANSFER ON POST-TRAUMA LOWER EYELID ECTROPION RECONSTRUCTION - Ulfa Elfiah; Dicky Primadika Aprinova (Jurnal Rekonstruksi dan Estetik)
Highlights: